Lidocaine could promote the cuproptosis through up-regulating the long noncoding RNA DNMBP-AS1 in Hep-2 cells - Wei Liu; Yi Yu; Yi He; Meihong Lv (BMC Cancer)
Abstract Background Lidocaine is a traditional local anesthetic, which has been reported to trigger apoptosis through the mitochondrial pathway, independent of death receptor signaling. Cuproptosis is a copper triggered mitochondrial cell death mode. In this study, we explored the biological effects of lidocaine on cuproptosis in Hep-2 cells and studied the relevant mechanisms. Methods quantitative RT-PCR was used to measure the expression level of long noncoding RNA (IncRNA) DNMBP-AS1. DNMBP-AS1 siRNA (si-DNMBP-AS1) were transfected into Hep-2 cells to verify the roles of DNMBP-AS1 in cuproptosis. 24 h treatment with 20 nM elesclomol and 2 µM CuCl2 was performed to promote the occurrence of Cuproptosis. Cell proliferation, migration and apoptosis assays ware utilized to analyze biological effect of lidocaine and DNMBP-AS1 on Hep-2 cells. Active caspase-3 were also determined after treatment. Results DNMBP-AS1 was significantly upregulated during cuproptosis in Hep-2 cells. The si-DNMBP-AS1 significantly increased the cell viability with nonactivated caspase-3, promoted the cell migration and suppress the cuproptosis. Lidocaine was cytotoxic to the Hep-2 cells in a dose- and time-dependent manner. Exposure to 10 µM of lidocaine for 24 h did not reduce the viability or activated the caspase-3, but significantly increased the expression of DNMBP-AS1, and promote the cuproptosis. Anymore, si-DNMBP-AS1 reversed the pro-cuproptosis function of lidocaine. Conclusions lidocaine was cytotoxic to Hep-2 cells in a time- and dose-dependent manner, promoted the cuproptosis through up-regulating DNMBP-AS1. The results of this study offered initial optimism that lidocaine could be used in an adjuvant or neoadjuvant fashion in cancer treatment.